THE ROLE OF JOB SATISFACTION IN MEDIATING THE EFFECT OF LEADERSHIP ON EMPLOYEE PERFORMANCE - Saiful Amin (MBA - Journal of Management and Business Aplication, 2020)
This study aims to determine the role of job satisfaction in mediating the relationship between leadership and employee performance. This research was conducted at Dira park Ambulu Jember. The population in this study were all employees of Dira park Ambulu Jember, totaling 186 employees. The sample used was 46 respondents chosen by random sampling. Data analysis method uses path analysis. To determine the role of job satisfaction in mediating the relationship between leadership and employee performance was analyzed using the sobel test. The results of this study indicate that leadership has a significant effect on job satisfaction and employee performance. The results of this study also showed that job satisfaction did not significantly influence employee performance. In the results of this study also explained that the variable job satisfaction cannot mediate the effect of the relationship between leadership on the employee performance of Amba Jember Park. Keyword:Leadership, Work Satisfaction, Employee Performance